2020
DOI: 10.1101/2020.10.19.345769
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Primed smooth muscle cells acting as first responder cells in disease

Abstract: Rationale; Vascular smooth muscle cell (VSMC) dysregulation is a hallmark of vascular disease, including atherosclerosis. In particular, the majority of cells within atherosclerotic lesions are generated from pre-existing VSMCs and a clonal nature has been documented for VSMC-derived cells in multiple disease models. However, the mechanisms underlying the generation of oligoclonal lesions and the phenotype of proliferating VSMCs are unknown. Objective; To understand the cellular mechanisms underlying clonal V… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…This is because artefactual molecular differences arising from culture conditions, matrix stiffness and other non-physiological factors will obscure differences reflective of the true VSMC phenotypic state or of the effects of specific genetic perturbations. Second, to properly map the mature/differentiated adult SM-AS network, we would need to compare its splicing profile with a cognate phenotypically switched network, ideally in vivo during, for example, injury response [3, 59]. This is achievable in rodent systems but very challenging to model with human VSMCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because artefactual molecular differences arising from culture conditions, matrix stiffness and other non-physiological factors will obscure differences reflective of the true VSMC phenotypic state or of the effects of specific genetic perturbations. Second, to properly map the mature/differentiated adult SM-AS network, we would need to compare its splicing profile with a cognate phenotypically switched network, ideally in vivo during, for example, injury response [3, 59]. This is achievable in rodent systems but very challenging to model with human VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…This switch is accompanied by major changes in the cellular transcriptome including loss of expression of the contractile marker network. More recently, with the advent of single cell RNA sequencing, we have been able to dissect these molecular changes in far greater detail and better appreciate the phenotype switching process and the heterogeneity underlying contractile VSMCs of different embryonic lineages [1][2][3][4][5]. However, most of our knowledge of the molecular networks characterising these VSMC states is centred around the mRNA abundance profiles of marker genes, leaving us, currently, with a view only of the transcriptional component of the VSMC transcriptome.…”
Section: Introductionmentioning
confidence: 99%
“…Existence of distinct subpopulations of SMCs in the vascular wall that have greater propensity for proliferation when exposed to pathological stimuli may also explain the varying nature of atherosclerotic progression in different types of arteries. 51,53,56 Benditt et al 57 first identified clonal populations in human atherosclerotic lesions, presumed to be mostly SMCs, and described intimal masses as benign tumors. These results were based on X chromosome-linked (X linked) inactivation (using glucose-6-phosphate dehydrogenase) as a rudimentary marker for clonal analysis, which lacks cell-type specificity.…”
Section: Smc Clonality In Atherosclerotic Plaquesmentioning
confidence: 99%
“…Existence of distinct subpopulations of SMCs in the vascular wall that have greater propensity for proliferation when exposed to pathological stimuli may also explain the varying nature of atherosclerotic progression in different types of arteries. 51,53,56…”
Section: Smc Clonality In Atherosclerotic Plaquesmentioning
confidence: 99%
See 1 more Smart Citation